Local Markets: Agrobiodiversity Reservoirs and Access Points for Farmers' Plant Propagation Materials - Heindorf, Claudia; Reyes-Agüero, Juan Antonio; van't Hooft, Anuschka (Frontiers in Sustainable Food Systems, 2021)
Local markets are access points to local agrobiodiversity and part of the informal seed systems on which most small-scale farmers worldwide depend. With the urgent need for more sustainable food systems, detailed studies about the local market’s food crop diversity contribute to a better understanding of local market’s role in a functioning rural food system. In particular, the products that farmers trade and also use for reproductive purposes are of interest, since they represent our genetic capital for food production. The aim of this study is to show the significance of rural markets for the use and in situ conservation of local food plant genetic resources. We analyzed the inter- and intraspecific food crop diversity of the products from local merchants in ten markets in the agrobiodiversity rich region of the Huasteca Potosina, Mexico. In total, we registered 275 different food crop products consisting of 99 botanical species that have a high intraspecific richness of 210 variants. The list included 49 species which are used for reproduction in farmers’ fields. The average number of variants suitable for reproduction at each market is 58.4. Further, our results show that the different richness parameters vary within and between the inventoried markets and correlate partially to different factors like market size and origin. We conclude that local markets in the Huasteca Potosina are important components of the rural food system by providing income and access to a great variety of local food plants, as well as to seeds and plant material for farming. Yet, the high proportion of unique and rare food crop products within and among the markets indicates that the diversity of local markets is not a guaranteed resource.